Implementation of the logistics train in the intralogistics system: A case study - Strnad David (De Gruyter, 2021)
Intralogistics contributes significantly to the proper functioning of business processes. When designing and solving intralogistics systems, it is necessary to take into account the specific conditions in the given enterprise. The technical design, as well as the composition of the trolleys in the design of the transport system, must respect the specificities of the goods transported as well as shelf life and quantity. The study presents, for example, the implementation of a tugger train into an intercompany system with a solution procedure that is adapted to specific operating conditions and ensures the smooth functioning of the supply process. It is a principle based on the use of a simulation model. During its creation, three original sequences were developed in the programming language SimTalk. Their application decreases the use of blocks from the simulation program by up to 65% and it was possible to model more detailed processes that would not be possible in terms of functionality by using classical blocks. Fifteen directions of the language SimTalk were applied in their creation. Two variables of the type Integer, two variables of the type Object, and one variable of the type Real were defined.